(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of this article to comprehend the rising enthusiasm for sharing brand content online much has been expounded on utilizing content marketing as a component of the organization’s marketing blend. Content marketing is commonly comprehended as sharing brand content by means of possessed media to increase earned media trying to energize discussions about the brand to make, among others, more brand awareness. This examination plans to give learning and comprehension of how content marketing influences client commitment from a buyer’s point of view. This article examines about the utilization of content marketing in organizations and how it conveys advantages to the organizations.